A comparison of the disease occurrence of cerebrovascular diseases, diabetes mellitus, hypertensive diseases, and ischaemic heart diseases among hospitalized older adults in Thailand - Passakorn Suanrueang (Scientific Reports, 2024)
Abstract This observational research analyzed public hospital data from the Thailand Ministry of Public Health website to investigate gender differences in four categories of non-communicable diseases (NCDs) affecting hospitalized senior Thai populations for 12 years. This study aimed to determine the cumulative effects and analyze the odds ratio (OR) according to ICD-10 cause categories for the data from 2010 to 2021, accounting for 1,327,093 cases in 2010 and 2,275,936 cases in 2021. The findings revealed statistically significant gender differences in four categories of NCDs. Men were found to be more likely than women to have two types of NCDs, as measured by the OR (95%CI): cerebrovascular diseases (OR 1.34–1.47, 95%CI 1.32–1.48), and ischaemic heart disease (OR 1.24–1.63, 95%CI 1.23–1.64). Conversely, diabetes mellitus (OR 0.64–0.84, 95%CI 0.63–0.85) and hypertensive disorders (OR 0.82–0.95, 95%CI 0.81–0.97) were discovered to have a lower likelihood of ratios related in men compared to women. However, the trend of all four NCDs in men has significantly increased every year: cerebrovascular diseases = 0.0093 year(s) + 1.3391, (R2 0.82, p-value 0.001); diabetes mellitus = 0.0171 year(s) + 0.6143, (R2 0.97, p-value 0.001); hypertension = 0.0125 year(s) + 0.8091, (R2 0.96, p-value 0.001); and ischaemic heart disease = 0.0345 year(s) + 1.1884, (R2 0.99, p-value 0.001). Gender, a crucial biological factor, contributes to variations in the prevalence of illness. As such, it is essential to prioritize the disease risk occurrence and preventive care for men and women separately, with a focus on implementing more detailed screening and detection strategies, as well as tailored interventions.